Answer:
f(x) = x³ - 8x² + 21x - 20
Explanation:
∵ x = a + bi is a root of f(x)
∴ x = a - bi is the second root of f(x)
∴ f(x) = x² - (sum of the roots)x + (the product of the roots)
∵ 2 - i is a root of f(x)
∴ 2 + i is the other root of f(x) ⇒ (conjugate to each other)
∵ The sum of the roots = 2 - i + 2 + i = 4
∵ The product of them = (2 - i)(2 + i) = 4 + 2i - 2i - i² = 4 + 1 = 5⇒i² = -1
∴ f(x) = x² - 4x + 5
∵ 4 is a root of f(x)
∴ x - 4 is a factor of f(x)
∴ f(x) = (x² - 4x + 5)(x - 4) = x³ - 4x² - 4x² + 16x + 5x - 20
∴ f(x) = x³ - 8x² + 21x - 20